THE EFFECT OF MOTIVATION TOWARDS EMPLOYEE PERFORMANCE FOR CAFE WORKERS IN MEDAN - Augustinus, Daniel Cassa; Halim, Cindy Febiola (Journal of Accounting and Management Innovation, 2021)
Marriott Cafe is a part of JW Marriott Hotel Medan which is the first and only International five-star luxury hotel in Medan and is managed by Marriott International. As the brand holds: service excellence is one of the most vital factors to the hotelâ€™s success, it gradually trains its entire staff to ensure a high level of service is received by all guests.Based on the theory and the experience of the writer duringinternship at the company, the intention of this research is to find out about â€œThe Influence of Motivation on Employee Performance at Marriott Cafe in Medanâ€. The main purpose of this research is to find out whether motivation influences employee performance.The quantitative research method with descriptive approachis used in this research to describe the current condition at the research objectby using online questionnaire with interval scale to develop a hypothesis. The number of samplesis from the population, 46 people. However, due to the limited time and condition faced recently, the returned number of questionnaire data is 38 people.The result of this research shows that motivation has 48.6%influence on employee performance. The remaining 51.4% is affected by other variables outside this research. The result of the hypothesis with t-test proved that the null hypothesis is rejected, and the alternative hypothesis is accepted which means that there is a relationship between motivation and employee performance.In conclusion, motivation and employee performance have a strong correlation and motivation positively and significantly influences employee performance. This research is useful for the company to have an insight into the subject discussed, and further research is required.Keywords: Hospitality Management, Motivation, Employee Performance